Immunotherapy for a POLE Mutation Advanced Non-Small-Cell Lung Cancer Patient - Fu, Yang; Zheng, Yue; Wang, Pei-Pei; Chen, Yue-Yun; Ding, Zhen-Yu (Frontiers in Pharmacology, 2022)
Currently, the predictive role of POLE mutations for immunotherapy is under intense investigation. The POLE gene encodes one of the four subunits of DNA polymerase important for DNA replication and repair. POLE mutations are related to other favorable predicative factors such as high expression of PD-L1, high TMB, and infiltration of CD8+ cells in the tumor microenvironment. No formal clinical trials studied the efficacy of immunotherapy in lung patients harboring POLE mutation, only few cases were mentioned in the literature. Besides, lung cancer patients are prone to brain metastasis, which is notorious for the unresponsiveness to chemotherapy. The efficacy of immunotherapy for brain metastasis is still controversial. Here, we described a case of POLEmt NSCLC patient with brain metastasis who was treated with immunotherapy. His brain lesions disappeared after treatment. Our report strongly supported the benefit of immunotherapy for advanced NSCLC patients with POLE mutation, even with brain metastasis.